Mushroom Diversity in Urban and Suburban Environment of Bhubaneswar, Odisha - Panda, J.; Gupta, N. (Mushroom Research, 2017)
The present investigation is an attempt to bring outa picture of mushrooms diversity in Bhubaneswar, Odisha. The survey were conducted from June 2016 to October 2016 in urban and sub-urban areas including road side plantation area, public gardens and some protected campus and garden. The average temperature was found to be 25.90Â°C to 32.21Â°C during this period. Samples were collected, morphological characteristics recorded and preserved in dried form. A total number of 72 species were found, in which 24 species of mushrooms from soil, 14 mushrooms from leaf litter, 12 from twig and 22 number of sample from decay of wood. Protected campus endowed with green vegetation were found to be good habitat for the more number of mushroom species. In this investigation, Ganodema lucidum, Trametes versicolor, Clavaria vermicularis, Schizophyllum commune, Macrolepiota procera found to be widely occurred.